The Role of Leadership in Bahamian Special Economic Zones - Jones, Kemie Alexander (International Journal of Bahamian Studies, 2021)
During Edward St. George’s tenure as co-chair of the Grand Bahama Port Authority, he was credited with providing a unique blend of leadership traits which resulted in the city of Freeport’s growth. While a great deal of research has been conducted on the role of economic variables in special economic zone growth, little analysis has been conducted on the role of leadership. This paper reviews relevant theories on leadership styles and uses a case study research method to develop a leadership profile of Edward St. George as compared to three of his immediate successors in leading the Grand Bahama Port Authority. The results indicate that core tenets of St. George’s leadership were authentic and transformational leadership styles, which were less emphasized by his successors. The results of this paper indicate greater consideration should be placed on these humanistic leadership styles in selecting Grand Bahama Port Authority leadership, in order to encourage greater inclusion and special economic zone growth.